Ação cardíaca da leucina em ratos wistar em hipertireoidismo experimental - Fidale, Thiago Montes (2013)
Leucine is a regulator of protein metabolism in vivo, and there is little information regarding its action on cardiac hypertrophy induced by experimental hyperthyroidism and its relationship to serum creatine kinase. The study aimed to verify the effect of leucine in cardiac hypertrophy and serum creatine kinase in rats with hyperthyroidism. 75 animals were used, divided into two large groups according to the length of the experiment, seven days Group (7D) and Group twenty-eight days (D 28), subsequently divided into five subgroups these being the control zero (C0-7 and C028 ) controls (C-7 and C-28), hormone (H-7 and H- 28), leucine (G-7 and G-28) and leucine + hormone (LH-7 and HL-28). Hyperthyroidism was induced by administration of daily 20μg/100 grams of levothyroxine sodium in aqueous suspension by gavage. Leucine was supplemented by adding 5% of the amino conventional diet. Blood was collected by cardiac puncture and analyzes made in kits for TSH, T3, T4 and CK-NAC CK-MB. At the end of the experiment the heart was removed and weighed. Subsequently, the left ventricle was separated together with the interventricular septum and heavy, was also performed to measure the transverse diameter of cardiomyocytes and compared between groups. The exercise tolerance was measured by the swim test and the intensity was determined in 7% of the weight of the animal. Blood pressure and heart rate were measured using a sphygmomanometer to rats tail, 4/25T ADInstruments PowerLab equipment ® and ® software ADInstruments LabChart 7. In statistical comparison was used analysis of variance (ANOVA) and two-way post-Tukey test, considering p values <0.05. In rats treated with thyroid hormone occurs, cardiac hypertrophy with increased weight of the left ventricle, increased heart rate and elevated concentrations of CK-MB after 28 days. The association of leucine seems to modulate hormone-induced cardiac hypertrophy in this experimental model, and reduce blood concentrations of CK-NAC and CK-MB by unknown mechanisms. Thyroxine increases the swimming performance of rats after therapy for 14 and 21 days but with performance drop in 28 days.